2013
DOI: 10.1002/rnc.3030
|View full text |Cite
|
Sign up to set email alerts
|

Interval observers for discrete-time systems

Abstract: SUMMARY Interval observers are constructed for discrete‐time systems. First, time‐invariant interval observers are proposed for a family of nonlinear systems. Second, it is shown that, for any time‐invariant exponentially stable discrete‐time linear system with additive disturbances, time‐varying exponentially stable discrete‐time interval observers can be constructed. The latter result relies on the design of time‐varying changes of coordinates, which transform a linear system into a nonnegative one. Copyrigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
73
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(73 citation statements)
references
References 22 publications
0
73
0
Order By: Relevance
“…In recent works (see for instance [19], [22] and [20]), it has been shown that it is always possible to relax this assumption by means of a change of coordinates z s = T s x s with a nonsingular matrix T s such that T s (μA s − L s C s )T −1 s is Metzler.…”
Section: Known Singular Perturbation Parameter Casementioning
confidence: 97%
“…In recent works (see for instance [19], [22] and [20]), it has been shown that it is always possible to relax this assumption by means of a change of coordinates z s = T s x s with a nonsingular matrix T s such that T s (μA s − L s C s )T −1 s is Metzler.…”
Section: Known Singular Perturbation Parameter Casementioning
confidence: 97%
“…In recent works [8], [3] and [23], it has been shown that it is possible to relax this assumption by means of a change of coordinates z = T x s with a nonsingular matrix T such that the matrix T (µ 0 A s − LC s )T −1 is Metzler.…”
Section: A Exact Interval Observersmentioning
confidence: 97%
“…Interval observer design problem for uncertain dynamical systems has received a great attention in the literature the last decades . In the case of linear systems, this problem has been tackled in both continuous‐time and discrete‐time framework .…”
Section: Introductionmentioning
confidence: 99%